2021
DOI: 10.11591/ijpeds.v12.i1.pp551-557
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive dynamic programming algorithm for uncertain nonlinear switched systems

Abstract: <p>This paper studies an approximate dynamic programming (ADP) strategy of a group of nonlinear switched systems, where the external disturbances are considered. The neural network (NN) technique is regarded to estimate the unknown part of actor as well as critic to deal with the corresponding nominal system. The training technique is simul-taneously carried out based on the solution of minimizing the square error Hamilton function. The closed system’s tracking error is analyzed to converge to an attract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Moreover, the speed controller is designed to keep the motor speed constant when speed is changed and the torque is changed (increase or decrease), the response of the controller is always stable. Compare the results with the studies in [15], and in [13], [18], the results of the paper are better with the simulation with the time to reach a smaller equilibrium value (0.04s), to satisfy the controller of the experimental part always works well with the large capacity motor many times (more than 10 times) This is one of the proven good results for the controller that has been designed. Observing experimental results with the position controller with variable structure, shows that the control system building using dSPACE 1104 card has brought good working quality, output is always close to the amount in balanced stable working process.…”
Section: The Experimental Researchmentioning
confidence: 51%
See 1 more Smart Citation
“…Moreover, the speed controller is designed to keep the motor speed constant when speed is changed and the torque is changed (increase or decrease), the response of the controller is always stable. Compare the results with the studies in [15], and in [13], [18], the results of the paper are better with the simulation with the time to reach a smaller equilibrium value (0.04s), to satisfy the controller of the experimental part always works well with the large capacity motor many times (more than 10 times) This is one of the proven good results for the controller that has been designed. Observing experimental results with the position controller with variable structure, shows that the control system building using dSPACE 1104 card has brought good working quality, output is always close to the amount in balanced stable working process.…”
Section: The Experimental Researchmentioning
confidence: 51%
“…Research on speed control loop synthesis with nonlinear control object as shown in Figure 1, the use of traditional linear controllers such as PID has not overcome the effects of uncertain nonlinear factors and variable parameters of the model to the working quality of the system, [3], [4], [9], [13]. By synthesizing the adaptive sliding mode controller, the negative influencing factors of friction, elasticity, the quality of the drive system have been solved [6], [10], [18].…”
mentioning
confidence: 99%
“…The parameters of the proposed controller ( 18 ). The simulations will focus on the command tracking effect of the proposed controller (18). It is clearly seen that, although the references are depended on time but the tracking effectiveness is guaranteed (Figures 5 and 6).…”
Section: The Simulation and Evaluation Of Research Resultsmentioning
confidence: 97%
“…To get an assessment of the quality of the proposed controller, the authors build simulations on MATLAB-Simulink for the model object of a ball screw system using an AC servo motor. This is a permanent magnet synchronous motor (PMSM) with a conventional proportional integral derivative (PID) controller and a slip controller has been proposed, [8], [9], [11]. Parameters VP, VI are selected on the basis of experimental method Zeigler Nichols.…”
Section: Resultsmentioning
confidence: 99%